SUITABILITY OF RICE HUSK ASH TREATED BLACK COTTON SOIL FOR WASTE CONTAINMENT APPLICATION (Malaysian Journal of Civil Engineering, 2018)
This paper presents an experimental study aimed at assessing the suitability of rice husk ash (RHA) treated black cotton soil as a barrier in Municipal Solid Waste (MSW) containment facility. Laboratory tests were conducted on black cotton soil treated with 5, 10 and 15% RHA at moulding water contents of 2 and 4% on both wet and dry sides of optimum moisture content (OMC) using British Standard Heavy (BSH) compactive effort. Index properties, hydraulic conductivity (k), volumetric shrinkage strain (VSS), and unconfined compressive strength (UCS) tests were conducted on all the samples. The results obtained indicated that the soil was classified as A-7-5(18) according to the American Association of States Highway and Transport Officials (AASHTO) classification system and Silt of high plasticity (MH) in accordance with the Unified Soil Classification System (USCS). It was observed that addition of RHA was accompanied with decrease in the plasticity index from 24 to as low as 3%. An improvement in the moisture-density relationship of the soils showed an increase in Maximum Dry Density (MDD) from 1.46 to 1.52 Mg/m3 as well as a decrease from 24.5 to 21.2% in OMC. The increase in RHA contents up to 10% brought about an improvement in the strength of the soil specimens by almost 332.4kN/m2 at 2% on the dry side of OMC. The VSS decreases with increase in RHA content to achieve the minimum shrinkage strain of 4.1% at 5% RHA treatment.